EFEKTIVITAS EDUKASI EMPAT PILAR PENATALAKSANAAN DIABETES MELITUS TERHADAP PENGETAHUAN, SIKAP, DAN PERILAKU PASIEN PROLANIS - Tya Yunitasari; Yuniarti Yuniarti; Sri Noor Mintarsih (Poltekkes Kemenkes Semarang, 2019)
Background : Diabetes mellitus is a metabolic disease characterized by higher blood sugar levels (hyperglycemia) caused by impaired insulin secretion, and insulin resistance or both. Diabetes mellitus in Semarang City in 2018 is the second non-communicable disease after hypertension with a total og 47248 cases. Kedungmundu Public Health Care is one of largest Public Health Care with cases of diabetes mellitus in Semarang City with a total 0f 3165 cases.Objective : The purpose of this study to determine the effect of education four pillars management type 2 diabates mellitus with WhatsApp social media apllication-based on education of knowledge, attiudes and behavior of type 2 diabetes mellitus in Prolanist participants atKedungmundu Public Health Care.Method : This research method using quasi-experimental pre - post test with control group design. The number of respondentwas 27 controls and 25 treatments. Data collected were knowledge, attitude, and behavior. The test used to determine the interaction between variables is the Wilcoxon test and paired T-test with 95% confidence level.Results : There is the influence of WhatsApp social media apllication-based on education of knowledge, attiudes and behavior (p value = 0.000).Conclusion : Providingeducation of four pillars management diabetes type 2 with WhatsApp media effective to improve knowledge, attitudes, and behavior prolanist participants.